Breast Cancer Cells Metastasize to the Tissue-Engineered Premetastatic Niche by Using an Osteoid-Formed Polycaprolactone/Nanohydroxyapatite Scaffold. (13th December 2021) - Xiong, Qisheng; Wang, Meng; Liu, Jinglong; Lin, Chia-Ying
Abstract : It has been deemed that the premetastatic niche (PMN) plays a critical role in facilitating bone metastasis of breast cancer cells. Tissue engineering scaffolds provide an advantageous environment to promote osteogenesis that may mimic the bony premetastatic niches (BPMNs). In this study, human mesenchymal stem cells (hMSCs) were seeded onto designed polycaprolactone/nanohydroxyapatite (PCL-nHA) scaffolds for osteogenic differentiation. Subsequently, a coculture system was used to establish the tissue-engineered BPMNs by culturing breast cancer cells, hMSCs, and osteoid-formed PCL-nHA scaffolds. Afterwards, a migration assay was used to investigate the recruitment of MDA-MB-231, MCF-7, and MDA-MB-453 cells to the BPMNs' supernatants. The cancer stem cell (CSC) properties of these migrated cells were investigated by flow cytometry. Our results showed that the mRNA expression levels of alkaline phosphatase (ALP), Osterix, runt-related transcription factor 2 (Runx2), and collagen type I alpha 1 (COL1A1) on the PCL-nHA scaffolds were dramatically increased compared to the PCL scaffolds on days 11, 18, and 32. The expression of CXCL12 in these BPMNs was increased gradually over coculturing time, and it may be a feasible marker for BPMNs. Furthermore, migration analysis results showed that the higher maturation of BPMNs collectively contributed to the creation of a more favorable niched site for the cancerous invasion. The subpopulation of breast cancer stem cells (BCSCs) was more likely to migrate to fertile BPMNs. The proportion of BCSCs in metastatic MDA-MB-231, MCF-7, and MDA-MB-453 cells were increased by approximately 63.47%, 149.48%, and 127.60%. The current study demonstrated that a designed tissue engineering scaffold can provide a novel method to create a bone-mimicking environment that serves as a useable platform to recapitulate the BPMNs and help interrogate the scheme of bone metastasis by breast cancer.